2000
DOI: 10.1093/jhered/91.4.289
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin inheritance and instability in purple basil (Ocimum basilicum L.)

Abstract: The instability of the purple pigments (anthocyanins) in purple basil varieties (Ocimum basilicum L.) limits their use as ornamental plants and as a potential anthocyanin source. Several self-pollinated generations of all purple plants were unsuccessful in stabilizing anthocyanin expression. In this study we investigated the inheritance and stability patterns of leaf traits using the Purple Ruffles variety. The results from the complete diallele crosses indicated anthocyanin expression in vegetative tissue is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 10 publications
1
33
0
Order By: Relevance
“…Hence, assessments of the visual effects of these cultivars were performed 60 days after sowing. Canopy volume; leaf shape, texture, size, and color; stem and flower color; and number of days to flowering were estimated according to studies containing basil characteristics which were developed by Phippen and Simon (2000) and Lorenzi and Souza (2001).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, assessments of the visual effects of these cultivars were performed 60 days after sowing. Canopy volume; leaf shape, texture, size, and color; stem and flower color; and number of days to flowering were estimated according to studies containing basil characteristics which were developed by Phippen and Simon (2000) and Lorenzi and Souza (2001).…”
Section: Methodsmentioning
confidence: 99%
“…Color variation is of great importance for ornamental plants trading along with dye production due to the presence of anthocyanin, especially in purple-colored leaf species (PHIPPEN and SIMON, 2000). Flowers and inflorescences are also essential for landscape composition.…”
Section: Introductionmentioning
confidence: 99%
“…Basils contain a wide range of essential oils rich in phenolic compounds (Phippen and Simon, 2000) and a wide array of other natural products including polyphenols such as flavonoids and anthocyanins. Epidemiological studies have suggested positive associations between the consumption of phenolic-rich foods or beverages and the prevention of disease (Scalbert and Williamson, 2000).…”
Section: Phytochemicals Responsible For the Therapeutic Effects Of Hementioning
confidence: 99%
“…Medicinal plants from the Lamiaceae family have been used since ancient times for their pharmaceutical properties (Bais et al 2002) due to the secondary metabolites such as phenolic compounds (including flavonoids and phenylpropanoids) as well as anthocyanins (Phippen and Simon 2000). Sweet basil (Ocimum basilicum L.) belonging to the Lamiaceae family is a rich source of phenolic antioxidant compounds and flavonoids (Juliani and Simon 2002;Jayasinghe et al 2003).…”
Section: Introductionmentioning
confidence: 99%